Epicardial adipose tissue microbial colonization and inflammasome activation in acute coronary syndrome. (1st June 2017) - Pedicino, Daniela; Severino, Anna; Ucci, Sara; Bugli, Francesca; Flego, Davide; Giglio, Ada F.; Trotta, Francesco; Ruggio, Aureliano; Lucci, Claudia; Iaconelli, Antonio; Paroni Sterbini, Francesco; Biasucci, Luigi M; et al.
Abstract: Background: Epicardial adipose tissue (EAT) has a close functional and anatomic relationship with epicardial coronary arteries. Accumulating evidence suggests that host microbiome alterations may play a role in several inflammatory/immune disorders, triggering a robust proinflammatory response also involving interleukin-1β (IL-1β) and the NALP3 inflammasome. In the current study, we explore the hypothesis that in patients with non-ST elevation acute coronary syndrome (ACS), EAT contains potentially pro-atherosclerotic bacteria that might elicit inflammasome activation. Methods: EAT samples were obtained during coronary artery bypass grafting from ACS ( n = 18) and effort stable angina (SA; n = 16) patients, and as controls, from patients with angiographically normal coronary arteries undergoing surgery for mitral insufficiency (MVD; n = 13). In all patients, NALP3 and proIL-1β mRNA expressions were evaluated with qRT-PCR. In 3 patients from each group, EAT microbiota composition was determined using next-generation sequencing technologies. Results: In EAT, mRNA expression of both NALP3 and pro-IL1β was significantly higher in ACS than in SA and MVD ( P = 0.028 and P = 0.005, respectively). A broad range of bacterial species ( n = 76) was identified in both ACS and SA, with different predominant species. In contrast, microbial DNA was barely observed in MVD. Conclusions: Our study demonstrated the presence of bacterial DNA directly into EAT, surrounding diseased coronary arteries, of patients with ACS. Furthermore, ACS is associated with NALP3/inflammasome pathway activation in EAT. Our data suggest that the EAT environment is susceptible to microbial colonization that might stimulate a proinflammatory response. These findings add new elements to the pathogenesis of ACS and suggest novel therapeutic targets. Highlights: Epicardial adipose tissue has a close relationship with epicardial coronary arteries. Bacterial DNA has been isolated directly from epicardial adipose tissue. NALP3/inflammasome pathway is activated in epicardial adipose tissue. These findings add new elements to the pathogenesis of acute coronary syndromes.